Novel Synonymous Variant in IL7R Causes Preferential Expression of the Soluble Isoform - Rafah Mackeh (14151225) (2024)
Purpose The interleukin-7 receptor (IL-7R) is primarily expressed on lymphoid cells and plays a crucial role in the development, proliferation, and survival of T cells. Autosomal recessive mutations that disrupt IL-7Rα chain expression give rise to a severe combined immunodeficiency (SCID), which is characterized by lymphopenia and a T−B+NK+ phenotype. The objective here was to diagnose two siblings displaying the T−B+NK+ SCID phenotype as initial clinical genetic testing did not detect any variants in known SCID genes. Methods Whole genome sequencing (WGS) was utilized to identify potential variants causing the SCID phenotype. Splicing prediction tools were employed to assess the deleterious impact of the mutation. Polymerase Chain Reaction (PCR), Sanger sequencing, flow cytometry, and ELISA were then used to validate the pathogenicity of the detected mutation. Results We discovered a novel homozygous synonymous mutation in the IL7R gene. Our functional studies indicate that this variant is pathogenic, causing exon 6, which encodes the transmembrane domain, to be preferentially spliced out. Conclusion In this study, we identified a novel rare synonymous mutation causing a loss of IL-7Rα expression at the cellular membrane. This case demonstrates the value of reanalyzing genetic data based on the clinical phenotype and highlights the significance of functional studies in determining the pathogenicity of genetic variants. Other Information Published in: Journal of Clinical Immunology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10875-024-01688-8